Total Abdominal Hysterectomy with Bilateral Salpingo-Oophorectomy with a History of Previous Surgery of Suicidal Intake of Hydrochloric Acid - Qayum, Mamuna; Akhtar, Salman; Ali, Osama; Ali, Waleed; Waheed, Nomira; Fatima, Tatheer (Pakistan Armed Forces Medical Journal, 2022)
A patient with a history of previous abdominal surgery is at increased risk of visceral injury due to adhesion and excessive bleeding, which may require surgical repair. The optimal outcome can be achieved with the inter-professional team, patient care after being discharged from the hospital, and follow-up after surgery for eight weeks. Here we present as case of total abdominal hysterectomy with bilateral salpingo-oophorectomy with a history of previous surgery of suicidal intake of Hydrochloric Acid.